2016
DOI: 10.14341/probl20166234-8
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphic marker Val109Asp in the omentin gene are associated with abdominal obesity in the Kyrgyz population

Abstract: Aim — in this study, we investigated whether polymorphisms Val109Asp in the omentin gene are associated with abdominal obesity in the Kyrgyz population.Material and methods. We genotyped 297 nonrelated adults Kyrgyz individuals. 127 patients (male — 46, female — 81, average age — 53±7,0) with abdominal obesity (elevated waist circumferences ≥102 cm for male subjects and ≥ 88 cm for female) and 170 non-obese control subjects (male — 107, female — 63, average age 51±9). Val109Asp polymorphisms analysis in the om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This may indicate the existence of a potential, more "thrifty" phenotype in these people. In the Kyrgyz population, it was confirmed that the genotype Val109Val in omentin gene increased the risk of abdominal obesity -one of the MetS components [18]. The results of our research are to some extent consistent with the results of the papers cited above, because in the adjusted model, carriers of the Asp allele (as compared to the carriers of the Val allele) showed quite a clear, though statistically insignificant, tendency to a lower risk of abdominal obesity (OR = 0.65; p = 0.169) and MetS (OR = 0.69; p = 0.181).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This may indicate the existence of a potential, more "thrifty" phenotype in these people. In the Kyrgyz population, it was confirmed that the genotype Val109Val in omentin gene increased the risk of abdominal obesity -one of the MetS components [18]. The results of our research are to some extent consistent with the results of the papers cited above, because in the adjusted model, carriers of the Asp allele (as compared to the carriers of the Val allele) showed quite a clear, though statistically insignificant, tendency to a lower risk of abdominal obesity (OR = 0.65; p = 0.169) and MetS (OR = 0.69; p = 0.181).…”
Section: Discussionmentioning
confidence: 93%
“…In the Caucasian population, however, no relationship was found between the mutations of the omentin gene and the occurrence of type 2 diabetes [17]. In the Kyrgyz population, however, it was noted that the genotype Val109Val in the omentin gene increased the risk of abdominal obesity -one of the MetS components [18]. In the available literature, no work has been published so far on the relationship between polymorphisms of the omentin gene and MetS.…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of abdominal obesity was associated with homozygous genotype Val109Val. Frequencies of Asp109Asp, Val109Asp, and Val109Val genotypes among individuals with abdominal obesity (48,40, and 12%, respectively) were different from those among control subjects (Asp109Asp -53%, Val109Asp -43%, and Val109Val -4%) [168]. Saremi et al examined the effects of 12 weeks of aerobic training on serum omentin-1 concentrations [169].…”
Section: Adipokinesmentioning
confidence: 99%